The conflict of laws - Clarkson, C. M. V. (Christopher M. V.); Hill, Jonathan, 1961- (Oxford ; New York : Oxford University Press, 2011)
This fourth edition covers traditional and new topics taught on international law courses, reflecting the profound changes that the subject has undergone in recent decades. Focusing on key principles in an engaging and approachable style, this text is essential for international law students.
Introduction -- Civil jurisdiction -- Foreign judgments -- Contractual obligations -- Non-contractual obligations -- Domicile, nationality and habitual residence -- Marriage -- Matrimonial causes -- Property.
Previous ed.: 2006.
Includes bibliographical references and index.
Keywords: Conflict of laws -- England